“King of the forage”—Alfalfa supplementation improves growth, reproductive performance, health condition and meat quality of pigs - Ma, Jixiang; Huangfu, Weikang; Yang, Xu; Xu, Junying; Zhang, Yan; Wang, Zhichang; Zhu, Xiaoyan; Wang, Chengzhang; Shi, Yinghua; Cui, Yalei (Frontiers in Veterinary Science, 2022)
As one kind of high quality feed with rich nutrients, including high quality protein and amino acids, dietary fiber, enriched vitamins and mineral elements and bioactive molecules, alfalfa has been widely used in the production of ruminant livestock. As the understanding of alfalfa becomes more and more comprehensive, it is found that the high quality nutrients in alfalfa could have positive effects on pigs. An increasing number of researches have shown that supplementing dietary alfalfa to the diet of gestating sows reduced constipation, alleviated abnormal behavior, improved satiety and reproductive performance; supplementing dietary alfalfa to the diet of piglets improved growth performance and intestinal barrier function, reduced intestinal inflammatory response and diarrhea; supplementing dietary alfalfa to the diet of growing-fattening pigs improved production performance and pork quality. Moreover, the mechanisms by which various nutrients of alfalfa exert their beneficial effects on pigs mainly including dietary fiber stimulating intestinal peristalsis, reducing constipation, increasing the activity of digestive enzymes, and promoting the colonization of beneficial bacteria in the intestinal tract through fermentation in the intestine, producing short-chain fatty acids and thus improving intestinal health; high quality protein and amino acids are beneficial to improve animal health condition; rich vitamins and mineral elements play an important role in various physiological functions and growth and development of the body; and bioactive molecules can improve the antioxidant and anti-inflammatory level. Therefore, alfalfa could be used as pig feed ingredient to alleviate various problems in the pig industry and to improve pig production performance. This review details the current application of alfalfa in pigs and the potential mechanisms of alfalfa to improve growth and reproductive performance, pork quality, as well as intestinal health, laying the foundation for the application of forage of high quality in pig production.